Contribution to eye-legged coordination, lumbar muscle power, and abdominal muscle strength versus shooting ability in WTW TC Grobogan U 13-15 Year-old - Adi, Pomo Warih; Fijaya, Septian Aldo (Fair Play, 2025)
The aim of this study is to find out the contribution of eye and leg coordination, limb muscle power, and abdominal muscle strength to shooting abilities in WTW football player TC Grobogan aged 13-15 years 2024. The data analysis results are presented as follows, (1) known using the Pearson product moment correlation with an eye-foot coordination significance value of 0.013 <0.05 meaning that there is a significant correlation. Eye-legged coordination gives an Effective Contribution of 19.3% to the Shooting ability. (2) The significance of the Node Muscle Power with Shooting capabilities is 0.037 < 0.05, meaning there is an important correlational relationship.